ANALISIS POTENSI WISATA BERBASIS WEB-GIS KABUPATEN SIJUNJUNG - Dela Syafmita; Rahmanelli Rahmanelli (JURNAL BUANA, 2020)
The purpose of this research is to explain and to analyze the potential of culture nature tourism and special interest based Web-GIS in Sijunjung Regency.The type of this research is descriptive with qualitative approach. Data used by research like secondary data and primary data. Object in this research about tourism potential in Sijunjung Regency and Web-GIS. Collected data technique are observation and documentation. Analyzed data technique are Web-GIS and description.The resulted of this research are: 1) culture nature tourism in Sijunjung Regency such as Timbulun waterfall in Tanjung Gadang Sub-district, Silokek Geopark and Ngalau Loguang in Sijunjung Sub-district, Tabek Silacan in IV Nagari Sub-District, and Ngalau Sisawah in Sumpur Kudus Sub-District. 2) culture nature tourism in Sijunjung Regency such as 13 rooms of Rumah Gadang, Makam Kerajaan Jambu Lipo, and Istano Lambu Suto in Lubuk Tarok Sub-District, Adat group of village and Makam Syekh Abdul Wahab in Sijunjung Sub-District, Makam Syekh M.Yasin in Koto VII Sub-District, Makam Rajo Ibadat in Sumpur Kudus. 3) special interest tourism culture in Sijunjung Regency such as Wahana Telabang Sakti in Kamang Baru Sub-District and Pemandian Air Panas in Sijunjung Sub-District. 4) tourism potential in Sijunjung Regency can be accessed in Web-GIS with domain address http://objekwisatakabupatensijunjung.000webhostapp.com.